2019
DOI: 10.1186/s13020-019-0235-z
|View full text |Cite
|
Sign up to set email alerts
|

A pair of new enantiomers of xanthones from the stems and leaves of Cratoxylum cochinchinense

Abstract: Background The simple and caged xanthones from Clusiaceae showed significant antineoplastic activity. This study aims to identify structural diverse xanthones and search for novel antitumor natural products from this family plants. Methods The structures of new compounds 1a and 1b were elucidated mainly through comprehensive NMR and MS spectroscopic data, and their absolute configurations were determined by the compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Most xanthone enantiomers reported in this period are prenylated; their structures are listed in Figure 17 (names see Table S17 in Supplementary Materials). Hua and coworkers reported a pair of diprenylated xanthone enantiomers 297a/297b with only one chiral center from Cratoxylum cochinchinense in 2019 [156]. The deoxoxanthone enantiomers 298a/298b and 299a/299b incorporating a phenylpropanoid unit were isolated from Uvaria valderramensis in 2014 [157].…”
Section: Xanthonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most xanthone enantiomers reported in this period are prenylated; their structures are listed in Figure 17 (names see Table S17 in Supplementary Materials). Hua and coworkers reported a pair of diprenylated xanthone enantiomers 297a/297b with only one chiral center from Cratoxylum cochinchinense in 2019 [156]. The deoxoxanthone enantiomers 298a/298b and 299a/299b incorporating a phenylpropanoid unit were isolated from Uvaria valderramensis in 2014 [157].…”
Section: Xanthonesmentioning
confidence: 99%
“…The flavane enantiomers 268a/268b were reported to show cytotoxicity against human Hep3B cells, and the dextroisomer 268b was obviously more active than the levoisomer 268a [146]. The xanthones 297a/297b were able to inhibit the proliferation of human HL-60 and MDA-MB-231 cancer cells, and the (−)-enantiomer 297b showed much stronger inhibitory activity than its (+)-enantiomer 297a against MDA-MB-231 cells [156]. The levorotatory enantiomer 312b was found to inhibit the proliferation of colorectal HCT-116 cell line with an IC 50 of 14.23 µM, but its antipodal enantiomer 312a was considered to be inactive [160].…”
Section: Cytotoxicitymentioning
confidence: 99%
“…This plant has been used as traditional medicines to treat several diseases such as fevers, diarrhea, ulcer, itches, coughs, edema and abdominal pain [10]. Additionally, the tender leaves are used to make tea products whereas the young fruit is used as food spice [11]. In Vietnam, the bark, roots, and leaves of C. cochinchinense are used for treatments of fevers, coughs, scabies, stomach aches, and eczema, whereas the twigs for scabies and burns [11].…”
Section: Introductionmentioning
confidence: 99%
“…As a deciduous shrub or tree, Cratoxylum cochinchinense belongs to the Clusiaceae plant family, in which some species have been used historically as traditional medicines ( Duan et al, 2012 ). Previous phytochemical investigations have indicated that the plants of Cratoxylum genus are rich in xanthones with extensive biological activities including anti-malaria, anti-bacteria, anti-HIV, and cytotoxicity ( Laphookhieo et al, 2006 ; Laphookhieo et al, 2009 ; Rattanaburi et al, 2014 ; Duan et al, 2015 ; Ito et al, 2017 ; Li et al, 2018 ; Huang et al, 2019 ; Jia et al, 2019 ; Lv et al, 2019 ). Some xanthones, e.g., gambogic acid, were found to have promising cytotoxic effects and be potentially useful for the discovery of anticancer lead compounds.…”
Section: Introductionmentioning
confidence: 99%